2000
DOI: 10.4049/jimmunol.164.9.4899
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors Determine the Contribution of Leukotrienes to Acute Inflammatory Responses

Abstract: Leukotrienes (LT) are potent lipid mediators synthesized by the 5-lipoxygenase pathway of arachidonic acid (AA) metabolism. LT have been implicated in a broad spectrum of inflammatory processes. To investigate the influence of genetic factors on the contribution of LT to acute inflammation, we generated congenic 5-lipoxygenase-deficient 129, C57BL/6 (B6), and DBA/1Lac (DBA) mouse lines. Topical application of AA evoked a vigorous inflammatory response in 129 and DBA mice, whereas only a modest response was see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 38 publications
(59 reference statements)
3
24
0
2
Order By: Relevance
“…We have previously reported that macrophages from 5-LO-deficient animals released increased amounts of PGE 2 and TXB 2 , compared with wild-type controls (30), and we found an enhanced role for prostanoids in several acute inflammatory processes in 5-LO-deficient mice (30,32). Furthermore, several studies have demonstrated enhanced production of COX metabolites, specifically TXB 2 , in rat (5, 10, 41) and dog (10, 42) models of allograft rejection, and that TXB 2 contributes to transplant rejection (4,5,8,10).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We have previously reported that macrophages from 5-LO-deficient animals released increased amounts of PGE 2 and TXB 2 , compared with wild-type controls (30), and we found an enhanced role for prostanoids in several acute inflammatory processes in 5-LO-deficient mice (30,32). Furthermore, several studies have demonstrated enhanced production of COX metabolites, specifically TXB 2 , in rat (5, 10, 41) and dog (10, 42) models of allograft rejection, and that TXB 2 contributes to transplant rejection (4,5,8,10).…”
Section: Discussionsupporting
confidence: 64%
“…Additional studies have demonstrated that the loss of 5-LO may result in enhanced synthesis and activity of other eicosanoids, particularly COX metabolites (30,32). Therefore, we explored the possibility that eicosanoid production may be altered in 5-LO-deficient allografts by measuring levels of TXB 2 (the stable metabolite of TXA 2 ) in cortical homogenates prepared from the transplanted kidneys and stimulated with the calcium ionophore A23187.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because inflammatory responses to leukotrienes have been previously shown to differ among mouse strains with different genetic backgrounds, 22 two strains of apoE Ϫ/Ϫ mice on a C57B/6 background (C57E Ϫ/Ϫ ) and apoE Ϫ/Ϫ mice on a mixed background of 1290la/BalbC (129E Ϫ/Ϫ ), and LDLr Ϫ/Ϫ mice on a C57B/6 background were treated with a LTB4 antagonist (CP-105,696). The two different strains of apoE Ϫ/Ϫ (C57E…”
Section: Analysis Of Lesionsmentioning
confidence: 99%
“…We chose 129 inbred strain because Goulet et al (32) CysLTs were detected in epidermis (data not shown). In the subcutaneous connective tissues, however, high expressions of CysLT 1 (Fig.…”
Section: Different Tissue Distribution Of Cyslt 1 and Cyslt 2 Mrna Inmentioning
confidence: 99%